Pengaruh Penggunaan E-Money, Literasi Keuangan, dan Pengelolaan Keuangan Pribadi Terhadap Perilaku Konsumtif Mahasiswa Akuntansi di Kota Batam - Sofia Agina Br Sembiring; Dian Efriyenti (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
The expansion of digital financial services, particularly electronic money, has significantly altered the way university students conduct financial transactions. Although e-money offers practicality and transactional efficiency, uncontrolled usage may lead to higher levels of consumptive behavior when it is not supported by sufficient financial literacy and effective personal financial management. This study examines the influence of e-money utilization, financial literacy, and personal financial management on the consumptive behavior of accounting students in Batam City. A quantitative research design was adopted using a survey approach. The study population comprised active undergraduate accounting students in Batam City, from which 272 respondents were selected through purposive sampling. Primary data were obtained through structured questionnaires using a five-point Likert scale and analyzed using multiple linear regression with SPSS. The findings reveal that e-money usage exerts a positive and statistically significant effect on consumptive behavior, whereas financial literacy and personal financial management demonstrate negative and significant effects. Collectively, the independent variables have a significant impact on students’ consumptive behavior, indicating that strengthening financial literacy and personal financial management can help mitigate consumptive tendencies amid the growing adoption of e-money.